A new species of the palaearctic genus Dasypoda Latreille 1802 (Hymenoptera: Dasypodaidae) from the Great Rift Valley in Ethiopia - Michez, Denis; Pauly, Alain (Zootaxa, 2012)
Dasypoda is a genus of solitary bees previously recorded as endemic in the Palaearctic region from Portugal to Japan. Wedescribe here a new species of Dasypoda (Hymenoptera, Apoidea, Melittidae), Dasypoda riftensis sp. nov., collected fromEthiopia, Great Rift Valley, Gallo. This species is the first record of the genus Dasypoda in Sub-Saharan Africa and is of phylogenetic importance. We discuss biogeographical implications of the record in Ethiopia.